2014
DOI: 10.1016/j.tem.2013.10.006
|View full text |Cite
|
Sign up to set email alerts
|

BDNF mediates adaptive brain and body responses to energetic challenges

Abstract: Emerging findings suggest that brain-derived neurotrophic factor (BDNF) serves widespread roles in regulating energy homeostasis by controlling patterns of feeding and physical activity, and by modulating glucose metabolism in peripheral tissues. BDNF mediates beneficial effects of energetic challenges such as vigorous exercise and fasting on cognition, mood, cardiovascular function and peripheral metabolism. By stimulating glucose transport and mitochondrial biogenesis BDNF bolsters cellular bioenergetics and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
334
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 459 publications
(377 citation statements)
references
References 97 publications
(104 reference statements)
8
334
0
7
Order By: Relevance
“…It is important to clarify that the levels of these neurotrophins can be influenced by various factors such as obesity and habitual physical activity [39][40][41][42]. BDNF is also expressed in adipose tissue and may be accompanied by elevated levels of cortisol, and a subliminal inflammatory process that occurs in obesity [39,40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to clarify that the levels of these neurotrophins can be influenced by various factors such as obesity and habitual physical activity [39][40][41][42]. BDNF is also expressed in adipose tissue and may be accompanied by elevated levels of cortisol, and a subliminal inflammatory process that occurs in obesity [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…BDNF is also expressed in adipose tissue and may be accompanied by elevated levels of cortisol, and a subliminal inflammatory process that occurs in obesity [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that retinol palmitate supplementation (1,000 to 9,000 IU/day -1 ) for 28 days decreased brain-derived neurotrophic factor (BDNF) in the rat hippocampus (De Oliveira et al 2011a). BDNF regulates neuronal plasticity, bioenergetics, mitochondrial biogenesis, and neuronal survival, to cite a few (Cheng et al 2010, Agrawal et al 2014, Marosi and Mattson 2014. Decreased BDNF may lead to limited mitochondrial biogenesis and mitochondrial dysfunction during events of neurotoxicity.…”
Section: Molecular Evidences Of Vitamin A-related Neurotoxicitymentioning
confidence: 99%
“…Neurotrophic factors are pivotal for many central nervous system functions such as neuronal survival, migration, and synaptogenesis 5) . In particular, BDNF plays crucial roles in the brain development, maintenance, and plasticity of neurons 6) , which contribute substantially to the prevention of depression and Alzheimer diseases through maintaining or improving memory and learn-ing function 7) . It is widely accepted that exercise training stimulates various signaling mechanisms that lead to BDNF upregulation, particularly in the hippocampus, thereby modulating cognitive functions by improving neurogenesis and neuronal activity [6][7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, BDNF plays crucial roles in the brain development, maintenance, and plasticity of neurons 6) , which contribute substantially to the prevention of depression and Alzheimer diseases through maintaining or improving memory and learn-ing function 7) . It is widely accepted that exercise training stimulates various signaling mechanisms that lead to BDNF upregulation, particularly in the hippocampus, thereby modulating cognitive functions by improving neurogenesis and neuronal activity [6][7][8][9][10] . Previous studies demonstrated that low-intensity exercise increased hippocampal BDNF and gene expression to a greater extent than moderate-or vigorous-intensity exercise 11,12) .…”
Section: Introductionmentioning
confidence: 99%